Modified metal organic porous material as well as preparation method and application thereof

By introducing PVP on H3BTB and using Co2+, Ni2+ and Cu2+ co-doping methods, the problem of degradation of skeleton collapse and adsorption performance of metal organic porous materials under high humidity conditions is solved, and the material is efficient under high humidity conditions is achieved Volatile organic matter adsorption extends service life and enhances the value of industrial application.

CN119386822APending Publication Date: 2025-02-07ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411695809.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing metal organic porous materials are prone to collapse or re-aggregation under high humidity conditions, resulting in a decrease in adsorption performance and shortening of service life. The adsorption efficiency of traditional adsorption materials to volatile organic matter under high humidity conditions is significantly reduced.

Method used

By introducing organic polymer polyvinyl acetamide (PVP) with a larger molecular weight and longer chains on H3BTB, and using Co2+, Ni2+ and Cu2+ co-doping as metal active centers, the structure of the material under high humidity conditions is enhanced. Stability and adsorption properties.

Benefits of technology

It significantly improves the structural stability of metal organic porous materials and the adsorption effect of volatile organic matter under high humidity conditions, extends the service life of the material, and provides a high-performance PVP-modified metal co-doped H3BTB material. It has high industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386822A_ABST
    Figure CN119386822A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of treatment of volatile organic compounds (VOCs), in particular to a modified metal organic porous material as well as a preparation method and application thereof. The modified metal organic porous material provided by the invention has high structural stability and excellent adsorption performance, and can ensure the adsorption treatment efficiency of volatile organic compound waste gas under a high-humidity working condition. The preparation method provided by the invention is simple and high in operability, has a remarkable adsorption effect on volatile organic compounds in a high-humidity working condition, and is easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of volatile organic compounds (VOCs) treatment, and in particular to a modified metal organic porous material and a preparation method and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) have a serious impact on the environment and ecology. The formation of haze, photochemical smog, fine particulate matter, secondary organic aerosols and ozone are all related to the excessive emission of VOCs. Most VOCs are also extremely harmful to human health and can cause chronic diseases, poisoning, teratogenicity, carcinogenicity, and even death. In order to improve the quality of the atmospheric environment and protect human health, appropriate VOC control measures must be taken. Adsorption has always been the mainstream technology in the field of industrial waste gas purification containing VOCs due to its low cost, low energy consumption and mature process. As the core, the most widely used and studied adsorption materials include carbon materials, zeolite molecular sieves, metal organic porous materials, etc.

[0003] Metal organic porous materials have attracted much attention due to their high specific surface area and pore volume, abundant active sites, flexible and adjustable pore size, and easy chemical modification. It is reported that the adsorption performance of metal organic frameworks for volatile organic compounds is far superior to traditional adsorbents such as activated carbon and silicon-based materials. 1,3,5-Tris(4-carboxyphenyl)benzene (H 3 As a three-coordinated bridged rigid ligand with a central symmetric structure, BTB is often used in the synthesis and performance research of metal organic porous materials due to its stable structure and diverse coordination modes. In recent years, the academic community has promoted the functionalization of polyoxometalate metal organic porous materials through modification, regulated their physical and chemical properties, and realized the application of such materials in gas adsorption and catalysis. However, due to the use of solutions in the production process of industrial enterprises and other reasons, the exhaust gas discharged by most enterprises often contains water vapor, and its content is between 10-70%. The presence of water molecules will not only cause the framework structure of metal organic porous materials to collapse or secondary agglomerate, but also compete with the target volatile organic molecules for adsorption, affecting the adsorption performance of metal organic porous materials for volatile organic compounds under high humidity conditions, which greatly limits the actual industrial application of metal organic porous materials in the field of volatile organic adsorption. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a modified metal organic porous material and a preparation method and application thereof, which are used to solve the problem that the efficiency of adsorbing volatile organic compounds by existing traditional adsorption materials such as carbon-based and silicon-based materials is significantly reduced under high humidity conditions, and the problem that the skeleton of the metal organic porous material collapses or re-agglomerates in the presence of water vapor, resulting in a decrease in adsorption performance and a shortened service life.

[0005] The preparation method provided by the present invention comprises the following steps: 3 Polyvinylpyrrolidone (PVP), an organic polymer with a larger molecular weight and longer chain, was introduced into BTB, and Co 2+ 、Ni 2+ and Cu 2+ Co-doping as a metal active center enhances the structural stability of the material under high humidity conditions, improves the adsorption capacity of metal organic porous materials for volatile organic compounds under high humidity conditions, effectively overcomes the shortcomings of the existing technology, and provides a feasible high-performance PVP modified metal co-doped H for the adsorption of volatile organic compounds under high humidity conditions. 3 BTB materials have high industrial application value.

[0006] In a first aspect, the present invention provides a method for preparing a modified metal organic porous material, the preparation method comprising the following steps:

[0007] S1. PVP and H 3 BTB was dissolved in anhydrous ethanol to obtain solution A, and then the solution A and the Co 2+ 、Ni 2+ , Cu 2+ Mix solution B with water until the solution becomes clear to obtain solution C;

[0008] S2, heating the solution C at a constant temperature under variable pressure conditions to react, and cooling to precipitate a solid product;

[0009] S3, washing and drying the solid product obtained in S2 to obtain the modified metal organic porous material.

[0010] PVP is a water-soluble polymer surfactant with hydrophilicity and polar groups. This property allows it to form a waterproof film on the surface of metal organic porous materials to protect them from water vapor erosion. PVP itself, as a capping agent, can adjust the relative growth rate of certain crystal faces in metal organic porous materials, control the morphology, shape and size of the material, and enhance its adsorption capacity for volatile organic compounds.

[0011] The present invention combines metals Co, Ni, and Cu with similar ion radii but different chemical properties into the same metal-organic porous material framework through metal doping. Compared with metal-organic porous materials of a single metal, the tri-metal organic porous material composed of doped metals can produce a multi-metal synergistic coordination effect, giving the material additional adsorption sites to improve the adsorption performance and stability of the metal-organic porous material under high-humidity conditions. In addition, its components are more controllable and its structure is more diversified.

[0012] In some embodiments of the present invention, the PVP and the H 3The mass ratio of BTB is 1:(1-5), for example, 1:1, 1:2, 1:3, 1:4, 1:5, etc.

[0013] In the present invention, the polymer chain of PVP can be adsorbed on H 3 BTB nucleus surface. When the doping amount of PVP increases, the pores formed on the surface of the material prepared by the present invention increase, and the adsorption capacity increases. However, if too much PVP is introduced, the pores will be blocked, resulting in a decrease in the specific surface area, which will in turn reduce the adsorption capacity and affect the adsorption effect. When the doping amount of PVP is too small, the hydrophobic ability of PVP is weakened, the water instability of the prepared material decreases, and the adsorption effect under high humidity conditions is reduced.

[0014] In some embodiments of the present invention, the H 3 The mass volume ratio of BTB to the anhydrous ethanol is 0.03-0.05 g / mL, such as 0.035 g / mL, 0.04 g / mL, 0.045 g / mL, etc.

[0015] In some embodiments of the present invention, the Co in solution B 2+ 、Ni 2+ , Cu 2+ The molar ratio is (0.5-2):(0.5-2):1, for example 1:1:1, 1:2:1, 1:1:2, 2:2:1, etc.

[0016] In some embodiments of the present invention, the Co 2+ The source is Co(NO 3 ) 2 6H 2 O.

[0017] In some embodiments of the present invention, the Ni 2+ The source is Ni(NO 3 ) 2 6H 2 O.

[0018] In some embodiments of the present invention, the Cu 2+ The source is Cu(NO 3 ) 2 ·3H 2 O.

[0019] In some embodiments of the present invention, the solvent of the solution B is water.

[0020] In some embodiments of the present invention, the Co in solution B 2+ 、Ni 2+ and Cu 2+The total concentration is 0.11-0.15 mol / L, for example 0.12 mol / L, 0.13 mol / L, 0.14 mol / L, etc.

[0021] In some embodiments of the present invention, the H 3 The molar amount of BTB and the Co 2+ 、Ni 2+ , Cu 2+ The total molar ratio is (1:1.5-2), for example 1:1.6, 1:1.7, 1:1.8, 1:1.9, etc.

[0022] In the present invention, due to the existence of steric hindrance, H 3 BTB and Cu 2+ 、Ni 2+ 、Co 2+ The ratio needs to be kept within an appropriate range. If the amount of metal ions added is too high, the metal ions and PVP will occupy each other, which will cause the PVP doping amount to decrease, and the water instability and adsorption effect of the material will be weakened. On the contrary, if the amount of metal ions added is too low, the PVP doping amount will increase, the material gaps will be easily blocked, and the adsorption effect will deteriorate.

[0023] In some embodiments of the present invention, step S2 is performed under an argon atmosphere.

[0024] In some embodiments of the present invention, step S2 is performed in a controllable pressure container.

[0025] In some embodiments of the present invention, the controllable pressure container has a pressure resistance greater than 3 bar.

[0026] In some embodiments of the present invention, the pressure change conditions in step S2 are: after maintaining 1 bar for 2-3 hours (for example, 2.2 hours, 2.5 hours, 2.8 hours, etc.), the pressure is uniformly increased to 2 bar within 2 hours, after maintaining 2 bar for 4-5 hours (for example, 4.2 hours, 4.5 hours, 4.8 hours, etc.), the pressure is uniformly increased to 3 bar within 2 hours, after maintaining 3 bar for 6-7 hours (for example, 6.2 hours, 6.5 hours, 6.8 hours, etc.), the pressure is uniformly reduced to 1 bar within 1 hour and maintained for 3-4 hours (for example, 3.2 hours, 3.5 hours, 3.8 hours, etc.).

[0027] The variable pressure condition of the present invention is conducive to the close combination of PVP attached to BTB and the three metal ions. If the tightness is too low, it will affect the adsorption capacity of the material, but if it is too high, the voids in the material will be reduced accordingly, which will also affect the adsorption capacity of the material.

[0028] In some embodiments of the present invention, the heating temperature in step S2 is 118-122°C, such as 119°C, 120°C, 121°C, etc.

[0029] In some embodiments of the present invention, the heating time is 20-24 hours, such as 21 hours, 22 hours, 23 hours, etc.

[0030] In some embodiments of the present invention, the cooling condition is cooling to below 15° C. within 10-12 min (eg, 10.5 min, 11 min, 11.5 min, etc.).

[0031] In some embodiments of the present invention, the washing solution in step S3 is a mixed solution of water and anhydrous ethanol.

[0032] In some embodiments of the present invention, the volume ratio of water to anhydrous ethanol is 1:(1-1.5), for example, 1:1.1, 1:1.2, 1:1.3, 1:1.4, etc.

[0033] In some embodiments of the present invention, the drying temperature in step S3 is 78-82°C, such as 79°C, 80°C, 81°C, etc.

[0034] In a second aspect, the present invention provides a modified metal organic porous material prepared by the preparation method described in the first aspect.

[0035] The modified metal organic porous material prepared by the voltage swing temperature control reaction method in the present invention is a trimetallic organic porous adsorption material with different molar ratios of Co, Ni and Cu (named PVP@Co / Ni / Cu-BTB), which has high structural stability and excellent volatile organic waste gas adsorption performance under high humidity conditions.

[0036] In a third aspect, the present invention provides an application of the modified metal organic porous material as described in the second aspect for adsorbing volatile organic compounds in an environment of 70-90% relative humidity, such as 75%, 80%, 85% relative humidity, etc.

[0037] The modified metal organic porous material provided by the present invention is suitable for adsorbing volatile organic waste gas (including but not limited to toluene, phenol, tetrahydrofuran, etc.) under high humidity conditions.

[0038] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:

[0039] The preparation method provided by the present invention has simple process and strong operability. The modified metal organic porous material prepared by the present invention is suitable for the adsorption treatment of volatile organic waste gas under high humidity conditions. The material structure stability is improved, the adsorption effect is significant, and it is easy to industrialize production. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0042] Figure 1 This is an electron microscope photograph of the modified metal organic porous material described in Example 1;

[0043] Figure 2 This is an electron microscope photograph of the modified metal organic porous material described in Example 2;

[0044] Figure 3 This is an electron microscope photograph of the modified metal organic porous material described in Example 3;

[0045] Figure 4 This is an electron microscope photograph of the modified metal organic porous material described in Example 4;

[0046] Figure 5 This is the XRD characterization diagram of the modified metal organic porous material described in Example 1;

[0047] Figure 6 This is the XRD characterization diagram of the modified metal organic porous material described in Example 2;

[0048] Figure 7 This is the XRD characterization diagram of the modified metal organic porous material described in Example 3;

[0049] Figure 8 This is the XRD characterization diagram of the modified metal organic porous material described in Example 4;

[0050] Fig. 9 This is the XRD characterization diagram of the modified metal organic porous material described in Comparative Example 1;

[0051] Fig.10 is an adsorption curve diagram of the modified metal organic porous material described in Example 1;

[0052] Fig.11 is an adsorption curve diagram of the modified metal organic porous material described in Example 2;

[0053] Fig.12 is an adsorption curve diagram of the modified metal organic porous material described in Example 3;

[0054] Fig.13is an adsorption curve diagram of the modified metal organic porous material described in Example 4;

[0055] Fig.14 This is the adsorption curve of the modified metal organic porous material described in Comparative Example 1. DETAILED DESCRIPTION

[0056] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0057] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0058] Example 1

[0059] This embodiment provides a modified metal organic porous material, and the preparation method thereof is as follows:

[0060] S1: Disperse and dissolve 0.5g PVP in 30mL anhydrous ethanol, stir until it is fully dissolved, then add 1g H 3 BTB and continue to stir and dissolve until the solution is clear and transparent to obtain solution A. In another beaker, Co(NO 3 ) 2 6H 2 O.Ni(NO 3 ) 2 6H 2 O, Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of distilled water to obtain solution B.

[0061] Solution A and solution B are mixed and stirred thoroughly until the solution is clear to obtain solution C, in which H 3 The molar amount of BTB and the metal ion Co 2+ 、Ni 2+ , Cu 2+ The total molar ratio is 1:1.8.

[0062] S2: Transfer solution C to a 100 mL stainless steel controllable pressure vessel and heat at 120°C for 24 hours. During this process, the pressure is first maintained at 1 bar for 3 hours, then increased to 2 bar at a constant rate within 2 hours and maintained for 5 hours, then increased to 3 bar at a constant rate within 2 hours, maintained at 3 bar for 7 hours, then reduced to 1 bar at a constant rate within 1 hour and maintained for 4 hours. After taking out, place in a freezer and cool to 15°C within 12 minutes.

[0063] S3: After the controlled pressure vessel is cooled to room temperature, the solid product is centrifuged and washed with a mixed solution of water and anhydrous ethanol in a volume ratio of 1:1 to remove unreacted H 3 BTB, and dried in a vacuum oven at 80 °C for 8 h to obtain a modified metal organic porous material powder (named PVP@Co 1 / Ni 1 / Cu 2 -BTB), the scanning electron microscope image of which is shown in Figure 1 shown.

[0064] Example 2

[0065] This embodiment provides a modified metal organic porous material (named PVP@Co 1 / Ni 1 / Cu 1 -BTB), the difference from Example 1 is that in step S1, Co 2+ 、Ni 2+ , Cu 2+ The molar ratio is 1:1:1. Figure 2 shown.

[0066] Example 3

[0067] This embodiment provides a modified metal organic porous material, and the preparation method thereof is as follows:

[0068] S1: Disperse and dissolve 0.5g PVP in 30mL anhydrous ethanol, stir until it is fully dissolved, then add 1g H 3 BTB and continue to stir and dissolve until the solution is clear and transparent to obtain solution A. In another beaker, Co(NO 3 ) 2 6H 2 O.Ni(NO 3 ) 2 6H 2 O, Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of distilled water to obtain solution B. Solution A and solution B were mixed and stirred until the solution was clear to obtain solution C, in which H3 The molar amount of BTB and the metal ion Co 2+ 、Ni 2+ and Cu 2+ The total molar ratio is 1:2.

[0069] S2: Transfer solution C to a 100 mL stainless steel controllable pressure container and heat at 122°C for 20 hours. During this process, the pressure is first maintained at 1 bar for 2 hours, then increased to 2 bar at a constant rate within 2 hours and maintained for 4 hours, then increased to 3 bar at a constant rate within 2 hours, maintained at 3 bar for 6 hours, then reduced to 1 bar at a constant rate within 1 hour and maintained for 3 hours. After taking out, place in a freezer and cool to 15°C within 10 minutes.

[0070] S3: After the controlled pressure vessel is cooled overnight to room temperature, the solid product is centrifuged and washed with a mixed solution of water and anhydrous ethanol in a volume ratio of 1:1.5 to remove unreacted H 3 BTB, and dried in a vacuum oven at 80 °C for 8 h to obtain a modified metal organic porous material powder (named PVP@Co 1 / Ni 2 / Cu 2 -BTB). SEM images are shown in Figure 3 shown.

[0071] Example 4

[0072] This embodiment provides a modified metal organic porous material, and the preparation method thereof is as follows:

[0073] S1: Disperse and dissolve 0.5g PVP in 30mL anhydrous ethanol, stir until it is fully dissolved, then add 1g H 3 BTB and continue stirring until the solution is clear and transparent to obtain solution A. In another beaker, Ni(NO 3 ) 2 6H 2 O、Co(NO 3 ) 2 6H 2 O, Cu(NO 3 ) 2 ·3H 2 O was dissolved in 30 mL of distilled water to obtain solution B. Solution A and solution B were mixed and stirred until the solution was clear to obtain solution C, in which H 3 The molar amount of BTB and the metal ion Co 2+ 、Ni 2+ and Cu 2+ The total molar ratio is 1:1.5.

[0074] S2: Solution C was transferred to a 100 mL stainless steel controllable pressure vessel and heated at 118°C for 22 hours. During this process, the pressure was first maintained at 1 bar for 3 hours, then increased to 2 bar at a constant rate within 2 hours and maintained for 4 hours, then increased to 3 bar at a constant rate within 2 hours, maintained at 3 bar for 7 hours, then reduced to 1 bar at a constant rate within 1 hour and maintained for 3 hours. After taking out, place in a freezer and cool to 15°C within 12 minutes.

[0075] S3: After the controlled pressure vessel is cooled overnight to room temperature, the solid product is centrifuged and washed with a mixed solution of water and anhydrous ethanol in a volume ratio of 1:1.2 to remove unreacted H 3 BTB, and dried in a vacuum oven at 80 °C for 8 h to obtain the modified metal organic porous material powder (named PVP@Ni 2 / Co 1 / Cu 2 -BTB). Scanning electron microscope image Figure 4 shown.

[0076] Comparative Example 1

[0077] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that the modified metal organic porous material does not contain Ni 2+ 、Co 2+ And PVP, step S1 H 3 The molar amount of BTB and the metal ion Cu 2+ The molar ratio is 1:1.8.

[0078] Comparative Example 2

[0079] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that the modified metal organic porous material does not contain Ni 2+ 、Co 2+ , H in step S1 3 The molar amount of BTB and the metal ion Cu 2+ The molar ratio is 1:1.8.

[0080] Comparative Example 3

[0081] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that the modified metal organic porous material does not contain Cu 2+ 、Co 2+ , H in step S1 3 The molar amount of BTB and the metal ion Ni 2+ The molar ratio is 1:1.8.

[0082] Comparative Example 4

[0083] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that the modified metal organic porous material does not contain Cu 2+ 、Ni 2+ , H in step S1 3 The molar amount of BTB and the metal ion Co 2+ The molar ratio is 1:1.8.

[0084] Comparative Example 5

[0085] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that in step S1, H 3 The molar amount of BTB and the metal ion Co 2+ 、Ni 2+ , Cu 2+ The total molar ratio is 1:3.

[0086] Comparative Example 6

[0087] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that the metal ion Co in solution B 2+ 、Ni 2+ , Cu 2+ The molar ratio is 1:1:5.

[0088] Comparative Example 7

[0089] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that the modified metal organic porous material does not contain PVP.

[0090] Comparative Example 8

[0091] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that the amount of PVP added in step S1 is 2 g.

[0092] Comparative Example 9

[0093] This comparative example provides a modified metal organic porous material, which is different from Example 1 in that step S2 is performed under constant pressure conditions, with the pressure being 1 bar.

[0094] Performance Testing

[0095] 1. XRD characterization

[0096] XRD analysis was performed on the modified metal organic porous materials prepared in Examples 1, 2, 3, 4 and Comparative Example 1. The results are as follows: Figure 5 , 6 , 7, 8, and 9. Fig. 9It can be seen that the modified metal organic porous material prepared in Comparative Example 1 has characteristic peaks at 2θ=6.8°, 9.6°, 11.65°, 13.5°, 17.5°, and 19.04°, which correspond to the (220), (222), (400), (422), (333), and (440) lattice planes of the Cu-BTB crystal, respectively. Its XRD spectrum is consistent with that of Cu-BTB reported in the literature, indicating the successful synthesis of Cu-BTB. Figure 5 , 6 , 7, and 8 show that the modified metal organic porous materials prepared in Examples 1, 2, 3, and 4 have characteristic peaks of Co-BTB, Ni-BTB, and Cu-BTB, and PVP is successfully loaded, and its peak position is basically similar to that of Cu-BTB in Comparative Example 1, but the intensity of some characteristic peaks changes, and the unit cell parameters are basically the same. This is because the electron densities of Co, Ni, and Cu are almost the same, and the metal atoms are randomly distributed in the same position in the lattice at a relative Co / Ni / Cu ratio. This shows that in the embodiments of the present invention, appropriate amounts of Co, Ni, and Cu are randomly distributed in the same position in the lattice in relative proportions, which can improve the adsorption capacity of the material.

[0097] 2. Specific surface area and toluene adsorption capacity test

[0098] The specific surface area of ​​the modified metal organic porous materials in the examples and comparative examples was tested by the following method:

[0099] The specific surface area and porosity were determined using an ASAP 2460 fully automatic surface area and porosity analyzer produced by Micromeritics Instruments, Inc., USA.

[0100] The modified metal organic porous materials of the embodiments and comparative examples and commercially available activated carbon (specific surface area 1149.47 m 2 ·g -1 ) was used to test the toluene adsorption capacity. The test conditions were a temperature of 25°C and relative humidity (RH) of 10%, 70%, 80%, and 90%, respectively.

[0101] The detection method is as follows:

[0102] At room temperature, a certain concentration of toluene waste gas is controlled to pass into a VOCs adsorption-desorption device equipped with adsorption material to start the reaction. The outlet toluene concentration is collected regularly and analyzed by gas chromatograph. When the outlet toluene concentration reaches 95% of the initial inlet toluene concentration and the measured toluene concentration ratio reaches 95% of the inlet within 30 minutes, the adsorption is considered to be saturated.

[0103] Adsorption capacity calculation:

[0104]

[0105] Where q is the saturated adsorption capacity of VOCs gas, mg·g -1 ;c 0 is the initial concentration of toluene in the inlet air, mg·m -3 ;c t is the toluene outlet concentration at time t, mg·m -3 ; F is gas flow rate, mL·min -1 ; t is the adsorption time, min; W is the loading amount of adsorption material, mg.

[0106] Table 1 Specific surface area and 80% RH exhaust gas adsorption capacity results

[0107] Case <![CDATA[Specific surface area m 2 ·g -1 > <![CDATA[Adsorption capacity mg·g -1 > Example 1 1296.85 164.26 Example 2 1151.15 149.42 Example 3 1251.12 158.91 Example 4 1250.96 152.48 Comparative Example 1 899.03 88.02 Comparative Example 2 991.71 111.01 Comparative Example 3 993.26 106.44 Comparative Example 4 1059.25 118.17 Comparative Example 5 1244.82 148.30 Comparative Example 6 1231.28 144.27 Comparative Example 7 1007.77 112.95 Comparative Example 8 1240.48 145.46 Comparative Example 9 1230.60 144.17

[0108] Table 2 Results of exhaust gas adsorption capacity at different RH

[0109]

[0110] The specific surface area results of the modified metal organic porous materials of the embodiments and comparative examples are shown in Table 1. As can be seen from Table 1, the specific surface area of ​​the modified metal organic porous materials prepared by the present invention is significantly increased, and the adsorption efficiency is improved.

[0111] The results of the adsorption capacity of toluene by the modified metal organic porous materials of the embodiments and comparative examples are shown in Table 1. As can be seen from Table 1, the adsorption capacity of the modified metal organic porous material prepared by the present invention under high humidity conditions is significantly increased compared with the modified metal organic porous material in the comparative example, indicating that the adsorption capacity of the modified metal organic porous material prepared by the present invention is significantly improved under high humidity conditions. Among them, the modified metal organic porous material prepared in Example 3 has a large metal loading, and its adsorption capacity is reduced by about 5% compared with that of Example 1; the modified metal organic porous material prepared in Example 4 has a small metal loading, and its material adsorption capacity is reduced by about 7% compared with that of Example 1.

[0112] Fig.10 , 11 , 12, 13, 14 are adsorption curves of Example 1, Example 2, Example 3, Example 4 and Comparative Example 1, respectively. Fig.10 and Fig.14 By comparison, it can be seen that the modified metal organic porous material PVP@Co prepared in Example 1 1 / Ni 1 / Cu 2 -BTB penetration time is increased by 50min compared to Cu-BTB with metal doping only. Fig.11 and Fig.14 By comparison, it can be seen that the modified metal organic porous material PVP@Co prepared in Example 21 / Ni 1 / Cu 1 -BTB penetration time is increased by 49min compared to Cu-BTB with metal doping only. Fig.12 and Fig.14 By comparison, it can be seen that the modified metal organic porous material PVP@Co prepared in Example 3 1 / Ni 2 / Cu 2 -BTB penetration time is increased by 50min compared to Cu-BTB with metal doping only. Fig.13 and Fig.14 By comparison, it can be seen that the modified metal organic porous material PVP@Co prepared in Example 4 2 / Ni 1 / Cu 2 -BTB penetration time is improved by 49 minutes compared with Cu-BTB doped with metal alone. Figure 10-14 The results show that the modified metal organic porous material prepared by the present invention still maintains a relatively stable structure under high humidity conditions.

[0113] The adsorption capacity results of the modified metal organic porous material and activated carbon in Example 1 under different humidity conditions are shown in Table 2. It can be seen from Table 2 that under 70%, 80% and 90% RH conditions, the adsorption capacity of the modified metal organic porous material in Example 1 is significantly higher than that of the activated carbon material, while under 10% RH conditions, there is no significant difference between the two, indicating that the adsorption effect of the modified metal organic porous material prepared by the present invention under high humidity conditions is significantly better than that of traditional carbon adsorption materials.

[0114] In summary, the modified metal organic porous material prepared in the present invention is 3 BTB introduces PVP, using Co 2+ 、Ni 2+ and Cu 2+ Co-doping as a metal active center enhances the structural stability of the material under high humidity conditions and improves the adsorption effect of the metal organic porous adsorption material on volatile organic compounds under high humidity conditions. The preparation method of the present invention is simple, highly operable, and has high industrial application value.

[0115] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0116] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features invented herein.

Claims

1. A method for preparing a modified metal organic porous material, characterized in that: The preparation method comprises the following steps: S1, dissolving PVP and H3BTB in anhydrous ethanol in turn to obtain solution A, and then mixing the solution A with a mixture containing Co 2+ 、Ni 2+ and Cu 2+ Mix solution B with water until the solution becomes clear to obtain solution C; S2, heating the solution C at a constant temperature under variable pressure conditions to react, and cooling to precipitate a solid product; S3, washing and drying the solid product obtained in S2 to obtain the modified metal organic porous material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the PVP to the H3BTB is 1:(1-5); Preferably, the mass volume ratio of H3BTB to anhydrous ethanol in step S1 is 0.03-0.05 g / mL.

3. The preparation method according to claim 1 or 2, characterized in that: The Co in solution B 2+ 、Ni 2+ , Cu 2+ The molar ratio is (0.5-2):(0.5-2):1; Preferably, the Co 2+ The source is Co(NO3)2·6H2O; Preferably, the Ni 2+ The source is Ni(NO3)2·6H2O; Preferably, the Cu 2+ The source is Cu(NO3)2·3H2O; Preferably, the solvent of solution B is water; Preferably, the Co in the solution B 2+ 、Ni 2+ and Cu 2+ The total concentration is 0.11-0.15 mol / L.

4. The preparation method according to any one of claims 1 to 3, characterized in that The molar amount of H3BTB and the Co 2+ 、Ni 2+ , Cu 2+ The total molar ratio is 1:(1.5-2).

5. The preparation method according to any one of claims 1 to 4, characterized in that: The step S2 is performed under an argon atmosphere.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The pressure change conditions in step S2 are: after maintaining 1 bar for 2-3 hours, the pressure is increased uniformly to 2 bar within 2 hours, after maintaining 2 bar for 4-5 hours, the pressure is increased uniformly to 3 bar within 2 hours, after maintaining 3 bar for 6-7 hours, the pressure is reduced uniformly to 1 bar within 1 hour and then maintained for 3-4 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The heating temperature in step S2 is 118-122°C; Preferably, the cooling condition is cooling to below 15°C within 10-12 minutes.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The washing solution in step S3 is a mixed solution of water and anhydrous ethanol; Preferably, the volume ratio of water to anhydrous ethanol is 1:(1-1.5); Preferably, the drying temperature in step S3 is 78-82°C.

9. A modified metal organic porous material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the modified metal organic porous material as claimed in claim 9 for adsorbing volatile organic compounds in an environment of 70-90% relative humidity.